A luminescent lyotropic liquid crystal with UV irradiation induced photochromism. Issue 5 (14th January 2020) - Li, Qingrun; Qiu, Juan; Liu, Hongguo; Chen, Xiao
Abstract : A lyotropic liquid crystal of photochromism by UV irradiation was fabricated through doping a unique europium complex with a protic ionic liquid as a solvent. Abstract : Multicolored photoluminescence induced by UV irradiation in soft materials has invaluable potential in display and detection applications. Here, an ionic liquid (ethylammonium nitrate, EAN)-mediated luminescent lyotropic liquid crystal (LLC) has been fabricated, where an europium complex with two ligands (Eu(DBM)3 BQ, DBM = dibenzoylmethane and BQ = 2, 2′-biquinoline) was doped. The obtained LLC exhibited enhanced fluorescence intensity and lifetime compared to those of Eu(DBM)3 BQ in EAN solution. Interestingly, the luminescent LLC color from the initial red emission of the complex was changed gradually to green when the UV exposure was extended. Though the DBM ligand displayed the typical photo-degradation, the emission intensity of BQ increased drastically. A mechanism based on an UV-induced trans -to- cis isomerization of BQ was proposed to explain such an unusual luminescence phenomenon. Both the experimental and computational results indicated an intra ligand charge transfer (ILCT) accompanied with the BQ isomerization under continuous UV irradiation, which resulted in the enhanced green light emission. The results obtained here are referable for better understanding the interplay between weak interactions and modulation of novel lanthanide-based photochromism systems under UV exposure.